Highly Diverse Synechococcus Pigment Types in the Eastern Indian Ocean - Zhang, Xiaodong; Cheung, Shunyan; Wang, Jing; Zhang, Guicheng; Wei, Yuqiu; Liu, Haijiao; Sun, Jun; Liu, Hongbin (Frontiers in Microbiology, 2022)
Marine picocyanobacteria Synechococcus exhibit highly diverse pigment types (PTs) and hence possess great advantage to utilize different spectrum of light effectively and to occupy a wide range of light niches. In this study, we explored the diversity of Synechococcus PTs in the eastern Indian Ocean (EIO), surface water of Strait of Malacca (SSM) and coastal waters of Sri Lanka (SSL). All the detected PTs were phycourobilin (PUB) containing PT 3 and showed distinct distribution patterns. Low PUB PT 3a and partial chromatic acclimater PT 3eA dominated in coastal and shallow waters (SSM and SSL). In contrast, high PUB and chromatic acclimaters PT 3dA and PT 3c/3dB were mainly distributed in open ocean (EIO). PT 3dA and PT 3c/3dB occurred at similar depths of the lower euphotic layers, but showed distinct distribution pattern that are partially exclusive, indicating they compete each other for the same light niche. Interestingly, the newly described PT 3f were detected with high relative abundances at all stations and particularly dominated in the upper euphotic layer in EIO, which was confirmed with PT-specific quantitative PCR (qPCR). The relative abundance of PT3f was negatively correlated with nutrient level, implying that PT 3f is adapted to oligotrophic waters. Pronounced niche partition of different PTs was observed in upper and lower layers of euphotic zone in EIO and SSM/SSL. Light, nutrients and strong stratification may play important roles in the niche partition of different PTs. Further analysis about ecologically significant taxonomic units (ESTU) revealed high diversity within each PT at different locations, which provided insights for understanding specific PT with wide range of niches.